Thalictrum punduanum var. hirtellum (Ranunculaceae), another new synonym of T. neurocarpum - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2020)
We have previously placed Thalictrum austrotibeticum (Ranunculaceae) in synonymy with T. neurocarpum. Based on critical observations on herbarium specimens and living plants in the wild, we demonstrate that T. punduanum var. hirtellum, recently described from southern Xizang (Tibet), China, is also identical with T. neurocarpum. We therefore reduce T. punduanum var. hirtellum to the synonymy of T. neurocarpum herein. We also further clarify the morphological distinction between T. neurocarpum and T. reniforme, which were often regarded as conspecific.